2009
DOI: 10.1111/j.1742-1241.2008.01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Switching patients from insulin glargine-based basal-bolus regimens to a once daily insulin detemir-based basal-bolus regimen: results from a subgroup of the PREDICTIVE™ study

Abstract: Patients with T1D and T2D may be switched from IGlarg to qd IDet as part of a basal-bolus regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
4
25
0
1
Order By: Relevance
“…The improvements in glycemic control observed in the current study conflict with results from the PREDICTIVE trial [13, 14] but are consistent with those from two US studies [15, 16]. In our study, the treatment persistence rate was significantly higher in the GLA-C group and medication adherence was significantly higher among GLA-S patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The improvements in glycemic control observed in the current study conflict with results from the PREDICTIVE trial [13, 14] but are consistent with those from two US studies [15, 16]. In our study, the treatment persistence rate was significantly higher in the GLA-C group and medication adherence was significantly higher among GLA-S patients.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the PREDICTIVE trial [13], the prevalence rate of hypoglycemia was lower after switching from insulin glargine to insulin detemir in the Medicare cohort in our study; however, the event rates were similar in both groups. No difference in hypoglycemia was observed in the commercially insured IMPACT ® population.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Yenigun et al reported on transition from insulin glargine to insulin detemir as a component of basal-bolus therapy within the PREDICITVE study [38]. Two subcohorts of 751 and 26 patients were defined based on prior basal-bolus treatment with glargine qd or glargine bid respectively, with or without OADs.…”
Section: Insulin Detemir In Basal-bolus Regimensmentioning
confidence: 99%
“…11,19 While Swinnen et al attempt to justify the rationale behind the twice-daily dosing regimen for detemir in L2T3, a discussion of what has been learned since the design of the study was not provided. Specifically, the authors make no mention of the numerous studies supporting the once-daily use of detemir, including randomized controlled trials and large observational studies 11,16,[19][20][21][22][23][24] and clamp and continuous glucose monitoring studies demonstrating comparable timeaction profiles between detemir and glargine. 25,26 In fact, according to the 2009 American Association of Clinical Endocrinologists=American College of Endocrinology guidelines, ''detemir can be used with 1 injection per day in patients with type 2 diabetes; excellent reproducibility of absorption profile within individuals; possibly less weight gain than with other insulins.''…”
mentioning
confidence: 97%